Accounting for Financialization: Stock-Flow-Consistent Political Economy. (1st July 2015) - ,; ,
Abstract : We adopt the Post Keynesian input-output framework pioneered by Wynne Godley to delve into both the causes and consequences of financialization. The distinction between National Income accounting and stock-flow-consistent modelling is showcased. Also, the political economy foundations of financial economics are unearthed. Constructively, the elements of a planned strategy to reinvent the accumulation of capital are sketched. Also, we show how ""asset-based reserve requirements"" and the issue of government bills and bonds can be ""creatively manipulated"" by the state to deliver superior and stable social outcomes.